Dicarbonyl stress and glyoxalases in ovarian function. (20th March 2014) - Tatone, Carla; Eichenlaub-Ritter, Ursula; Amicarelli, Fernanda
Abstract : The ovary is the main regulator of female fertility. Changes in maternal health and physiology can disrupt intraovarian homoeostasis thereby compromising oocyte competence and fertility. Research has only recently devoted attention to the involvement of dicarbonyl stress in ovarian function. On this basis, the present review focuses on clinical and experimental research supporting the role of dicarbonyl overload and AGEs (advanced glycation end-products) as key contributors to perturbations of the ovarian microenvironment leading to lower fertility. Particular emphasis has been given to oocyte susceptibility to methylglyoxal, a powerful glycating agent, whose levels are known to increase during aging and metabolic disorders. According to the literature, the ovary and the oocyte itself can rely on the glyoxalase system to counteract the possible dicarbonyl overload such as that which may occur in reproductive-age women and patients with PCOS (polycystic ovarian syndrome) or diabetes. Overall, although biochemical methods for proper evaluation of dicarbonyl stress in oocytes and the ovarian microenvironment need to be established, AGEs can be proposed as predictive markers and/or therapeutic targets in new strategies for improving reproductive counselling and infertility therapies.